Answer:
(x+y)² =(x+y)(x+y) Then you FOIL (First, outer, inner, last)
(x+y)² =(x+y)(x+y) = xx + xy + xy + yy [and when you combine like terms] = x² + 2xy + y²
(x+y)3 = (x² + 2xy + y²)(x+y) Then you FOIL (First, outer, inner, last)
(x+y)3 = (x² + 2xy + y²)(x+y) = x2x +2xxy + xy2 + x2y + 2xyy + y2y [and when you combine like terms] = x3 + 3x2y+ 3xy2 + y3
Step-by-step explanation:
Substitution.
Here is an example.
Let x be equal to 3 and y equal to 3.

From this we can conclude that the values of both x and y are equal to three therefore x and y have the same value and are equal.

Here in your case we have:

Hope this helps.
r3t40
The option D) x + x+2 + x+4 = 53 represents the exact equation of sum of three consecutive odd integers which is equal to 53.
<u>Step-by-step explanation:</u>
The sum of the three consecutive odd integers = 53
<u>To frame the equation :</u>
- Let us consider any of the three consecutive odd integers.
- Let us take 1,3,5 as the three consecutive odd integers.
Assume the first odd integer as 'x'. In this case, (x=1)
- The second consecutive odd integer is 3.
- The difference between 1 and 3 is 2.
Therefore, the second consecutive odd integer is x+2.
- The third consecutive odd integer is 5.
- The difference between 1 and 5 is 4.
Therefore, the third consecutive odd integer is x+4.
This means that, the sum of any three consecutive odd integers are given as x + x+2 + x+4.
Given that,
Sum of the three consecutive odd integers is 53.
The first odd integer + second odd integer + third odd integer = 53
x + x+2 + x+4 = 53.
The option D) x + x+2 + x+4 = 53 represents the exact equation of sum of three consecutive odd integers which is equal to 53.
Answer:
YourMom Not Cool
Step-by-step explanation:
yourMom is not cool
STOP CHEATING AND TRYING TO SEE ANSWER